2019
DOI: 10.3389/fphar.2019.01015
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17A Participates in Renal Inflammation Associated to Experimental and Human Hypertension

Abstract: Hypertension is now considered as an inflammatory disease, and the kidney is a key end-organ target. Experimental and clinical studies suggest that interleukin 17A (IL-17A) is a promising therapeutic target in immune and chronic inflammatory diseases, including hypertension and kidney disease. Elevated circulating IL-17A levels have been observed in hypertensive patients. Our aim was to investigate whether chronically elevated circulating IL-17A levels could contribute to kidney damage, using a murine model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 76 publications
0
37
0
Order By: Relevance
“…The involvement of redox processes in IL-17A actions has also been described in endothelial and immune cells [66]. Another important signal activated by IL-17A includes the protein kinases, such as RhoA/Rho-kinase, MAPK cascade, and Akt signaling [33,64,66] (Figure 3).…”
Section: Il-17a As a Proinflammatory Mediator In Dnmentioning
confidence: 95%
See 3 more Smart Citations
“…The involvement of redox processes in IL-17A actions has also been described in endothelial and immune cells [66]. Another important signal activated by IL-17A includes the protein kinases, such as RhoA/Rho-kinase, MAPK cascade, and Akt signaling [33,64,66] (Figure 3).…”
Section: Il-17a As a Proinflammatory Mediator In Dnmentioning
confidence: 95%
“…Thus, IL-17A/NF-κB pathway activation contributes to renal inflammation under diabetic conditions. We have recently described that systemic administration of IL-17A in C57BL/6 mice significantly upregulated kidney Mcp-1 and Rantes gene expression and recruited inflammatory cells to the kidney [64]. Moreover, in experimental angiotensin II induced renal damage, IL-17A neutralization also decreased proinflammatory genes and inflammatory cell infiltration [64,93].…”
Section: Il-17a As a Proinflammatory Mediator In Dnmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, studies in murine models of hypertension identified γδ T lymphocytes as the main source of IL-17A in hypertrophic hearts [ 59 ], kidneys, and aorta [ 60 ]. Moreover, IL-17A + γδ T lymphocytes were observed in the kidney of patients with hypertensive nephroangiosclerosis [ 61 ]. Currently, there are studies that identified the presence of γδ T lymphocytes in the peritoneal cavity and its relationship with Th17 response.…”
Section: Il-17a: a Key Proinflammatory Cytokine And Therapeutic Tamentioning
confidence: 99%